Major Congenital Malformations Among The Newborns in BSMMU Hospital (Bangladesh Medical Journal, 2012)
Congenital anomalies make an important contribution to infant mortality and they remain a leading cause of death in many countries of the world. Many babies also died in our country due to congenital anomalies. So this study was done to find out proportion, types of congenital anomalies at birth and immediate outcome of anomalous neonates. This cross sectional study was carried out in the department of Obstetrics and Gynecology, Bangabandhu Sheikh Mujib Medical University (BSMMU) Hospital Shahbagh, Dhaka during the period January 2007 to December 2007. All the women giving birth to babies with congenital anomalies during this period were included. Types of congenital anomalies in neonates were recorded. Diagnosis of congenital anomalies was based on ultrasonography and clinical evaluation of the newborn was done by experienced neonatologist. During the study period 1630 patients delivered, of which 60 had congenitally malformed babies making the occurance of 3.68%. Neural tube defect was found to be the commonest (33.33%) type of anomaly. Among the most frequent NTD was hydrocephalus. DOI: http://dx.doi.org/10.3329/bmj.v40i1.9955 BMJ 2011; 40(1): 7-12